LAVENDER AROMATHERAPY INTERVENTION ON SLEEP DISORDERS IN THE ELDERLY: A CASE STUDY - PUTRI ERNASARI; T WIDYA NARALIA (NURSING ANALYSIS: Journal of Nursing Research, 2022)
ABSTRACTBackground: Sleep disturbance is a disorder of a person's sleep pattern that will cause a decrease in sleep quality which has an impact on the health of the sufferer. If not addressed, it will have an impact on decreasing the quality of life, productivity and safety of the sufferer. Interventions that can be given to overcome sleep quality are lavender aromatherapy non-pharmacological therapy, namely relaxation techniques using concentrations of essential oils from plants. Lavender has the main content, namely Linalool Acetate which is able to relax and relax the working system of the nerves and muscles, providing a relaxing and calming effect. Methods: This study uses a descriptive type of research with a case study design approach that seeks to explain, understand, and explore a system methodologically regarding events that occur in an object of research. Objective: This study aims to identify the administration of lavender aromatherapy to improve sleep quality in the elderly with sleep problems. Results: Research conducted on the three respondents showed an increase in sleep quality and positive changes in the sleep quality of the elderly with a PSQI score of 4 (good). Conclusion: This study describes the intervention of giving Lavender Aromatherapy to improve the sleep quality of the elderly. Keywords: Lavender Aromatherapy, Sleep Quality, Elderly INTERVENSI AROMATERAPI LAVENDER TERHADAP GANGGUAN TIDUR PADA LANSIA: STUDI KASUS ABSTRAKLatar belakang: Gangguan tidur merupakan kelainan dari pola tidur seseorang yang akan menimbulkan penurunan kualitas tidur yang berdampak pada kesehatan penderitanya. Jika tidak diatasi akan berdampak pada penurunan kualitas hidup produktivitas dan keselamatan penderitanya. Intervensi yang dapat diberikan untuk mengatasi kualitas tidur adalah terapi non-farmakologi aromaterapi lavender yaitu tehnik relaksasi menggunakan konsentrasi minyak esensial dari tumbuhan. Lavender memiliki kandungan utama yaitu Linalool Asetat yang mampu mengendorkan dan melemaskan sistem kerja urat-urat saraf dan otot-otot, memberikan efek relaksasi dan ketenangan. Metode: Penelitian ini menggunakan jenis penelitian deskriptif dengan pendekatan case study design yang berusaha untuk menjelaskan, memahami, dan mengeksplorasikan suatu sistem secara metodelogi mengenai peristiwa yang terjadi dalam suatu obyek penelitian. Tujuan: Penelitian ini bertujuan untuk teridentifikasi pemberian aromaterapi lavender untuk meningkatkan kualitas tidur pada lansia dengan masalah gangguan tidur. Hasil: Penelitian yang dilakukan pada ketiga responden menunjukkan adanya peningkatan kualitas tidur dan perubahan positif pada kualitas tidur lansia dengan skor PSQI 4 (baik). Kesimpulan: Penelitian ini menggambarkan intervensi Pemberian Aromaterapi Lavender dapat meningkatkan kualitas tidur lansia. Kata kunci: Aromaterapi Lavender, Kualitas Tidur, Lansia